Why neotypification of Lophorina superba (Pennant, 1781) (Aves: Paradisaeidae) is justified—and necessary - Schodde, R.; Christidis, L.; Batalha-Filho, H.; Ericson, P.g.p.; Irestedt, M. (Zootaxa, 2021)
We review Irestedt et al.’s (2017) neotypification of the senior species name superba Pennant, 1781 in the bird-of-paradise genus Lophorina in response to Elliott et al. (2020) who challenged the resultant shift in name from the small isolate in New Guinea’s Vogelkop to the widespread species in the island’s central cordillera. In nine male plumage traits which differentiate the two species, six of which had been identified as novel by Irestedt et al., we show that the only two figures of the perished male holotype of superba match the central cordillera species more closely than the Vogelkop. We find as well that not only was the trading of bird-of-paradise skins from the central cordillera to coastal ports in the Vogelkop feasible before European contact, but application of superba to the central cordillera species also promotes nomenclatural stability: the name has been used overwhelmingly at species rank for that widespread form throughout post-19th century media. Re-assessment of Irestedt et al.’s point-by-point justification of neotypification under Article 75.3 of the ICZN (1999) Code establishes, furthermore, that their case meets the requirements of every condition specified in the article; the neotypification is thus valid. Elliott et al.’s alternative to fix superba to the Vogelkop isolate by type locality restriction is not Code-compliant, nor is their evidence for interpreting J.R. Forster as the author of the name. In conclusion, we lay out the correct nomenclature for the taxa of Lophorina under the Code.